A Comparison of Bacteriological Culture, Serology, and Quantitative PCR for Detecting Brucellosis in Ewes with a History of Abortion - Mohammad Javad Aminzadeh; Hamideh Kalateh Rahmani; Khadijeh Hashemi; Narges Khaleghnia; Mohammad Azizzadeh; Pezhman Mirshokraei (The Iranian Journal of Veterinary Science and Technology, 2023)
The zoonotic disease brucellosis is a serious public health and livestock industry concern. In the present study, we used bacteriological culture, RBT, and qPCR to determine the prevalence of brucellosis in the serum and milk samples of sheep with a history of abortion. Serum and milk samples were obtained from 100 sheep aged 3-5 years. In order to determine the prevalence of brucellosis, a modified RBT was performed on serum samples, Brucella was isolated from milk by bacteriological culture, and qPCR was applied to detect bacterial DNA in milk. The prevalence of brucellosis using modified RBT, bacteriological culture, and qPCR was 32%, 42%, and 44%, respectively. By considering qPCR as the standard, modified RBT showed a sensitivity of 95%, a specificity of 100%, an accuracy of 98%, a PV+ of 100%, and a PV- of 97%. The sensitivity, specificity, accuracy, PV+, and PV- for bacteriological culture were 77%, 100%, 90%, 100%, and 85%, respectively. The agreement between qPCR and modified RBT was 0.959 (95% CI: 0.896-1), between qPCR and bacteriological culture was 0.792 (95% CI: 0.667-0.897), and between modified RBT and bacteriological culture was 0.831 (95% CI: 0.709-0.38). Based on the results, bacterial isolation from sheep milk is not recommended except in specific cases due to its low sensitivity, as well as its time-consuming and hazardous nature. However, the modified RBT can be used as a routine method because of its cost-effectiveness, higher sensitivity, and higher accuracy compared to bacterial isolation. Moreover, qPCR is recommended as the gold standard test for detecting brucellosis in sheep milk, especially in those with a history of abortion.